2013
DOI: 10.21608/jpp.2013.73012
|View full text |Cite
|
Sign up to set email alerts
|

EFFECT OF FOLIAR SPRAY WITH SOME MICRONUTRIENTS ON GROWTH, YIELD AND CHEMICAL COMPOSITION OF PIGEON PEA (Cajanus cajan) UNDER ISMAILIA REGION CONDITIONS

Abstract: Spraying pigeon pea plants with Fe, Mn and Zn at 100 or 200 mg/l increased average pod number/plant, total fresh weight and seed yield compared with control (unsprayed). Mn at 100 mg/l gave the highest fresh yield and seed yield/feddan. Also, spraying pea plants with Mn at 100 mg/l increased vine yield as green fresh forage (16.35 ton/fed) followed by spraying pea plants with Zn at 100 mg/l (15.90 ton/fed).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 3 publications
1
2
0
Order By: Relevance
“…The addition of amino acids (polyamine precursors) has, on the other hand, resulted in an increase in chl b in both cultivars (Tyagi et al, 2023). Similar results have been reached with garlic plants (El-Shabasi et al, 2005), and sweet pepper (Tyagi et al, 2023) Al-Said & Kamal, 2008. This increase may be due to the role of amino acid mixture in detoxification of harmful accumulated of ROS in the thylakoid membrane during photosynthesis.…”
Section: Discussionsupporting
confidence: 66%
“…The addition of amino acids (polyamine precursors) has, on the other hand, resulted in an increase in chl b in both cultivars (Tyagi et al, 2023). Similar results have been reached with garlic plants (El-Shabasi et al, 2005), and sweet pepper (Tyagi et al, 2023) Al-Said & Kamal, 2008. This increase may be due to the role of amino acid mixture in detoxification of harmful accumulated of ROS in the thylakoid membrane during photosynthesis.…”
Section: Discussionsupporting
confidence: 66%
“…Amino acids are essential building blocks for the production of proteins, plant tissue, and chlorophyll. El-Shabasi et al (2005) discovered that treatments with plant-based amino acids considerably enhanced plant development and its constituent parts. El-Desouky et al ( 2011) on tomatoes and Abo Sedera et al (2010) on strawberries both reported similar effects and conclusions for plant-based and other essential amino acids.…”
Section: Discussionmentioning
confidence: 99%
“…In this respect, it has been stated that foliar supplementation of AAs improves vegetative growth, quantity and quality in Solanum tuberosum (Mobini et al, 2014), garlic (El-Shabasi et al, 2005) and bean (Abdel-Mawgoud et al, 2011). In another publication, the foliar application of amino acid mixtures to broccoli seedlings significantly increased growth of the roots and shoots (Shekari and Javanmardi, 2017).…”
Section: Growth Characteristicsmentioning
confidence: 99%